Examining the mental health literacy and challenges to supporting students among regional Philippine teacher education faculty - Julius Satparam (Camarines Sur Polytechnic Colleges, 2023)
Mental health has become an increasingly important public health issue as it plays a vital role in modern society. The education sector, for example, has become a common focus of mental health studies as students and teachers are subject to frequent social interactions and academic pressure. To better understand how equipped students and teachers are in addressing mental health-related issues, taking a look at their mental health literacy is essential. In the Philippines, the mental health literacy of teachers remains an untapped area of research yet to be explored and understood. The current study aimed to a) examine the mental health literacy of faculty in a regional Philippine teacher education institution and b) identify the challenges met by the faculty in providing needed help to students with mental health-related issues.  A total of forty-four faculty participated in the study and answered a mental health literacy scale. The average mental health literacy score of the overall sample was 114.45. This was found to be relatively higher than the scores of K-12 teachers but relatively lower than the scores of university students, healthcare professionals, athletic coaches and therapists, and members of the community. The challenges met by the respondents in providing needed help to students include lack of self-efficacy, resistance of students, conflicting values with the students, and lack of time. This study has provided evidence on the current mental health literacy level of regional teacher education faculty and the challenges they encounter in supporting students; insights gained from it may inform mental health-related professional development initiatives. Implications and limitations of the findings are discussed.